Implementasi Kebijakan Bantuan Pangan Non Tunai Dalam Rangka Pengatasan Kemiskinan DI Era Covid - 19 - Ariesta, Haura; Nugroho, Fentiny (UI Scholars Hub, 2023)
This study focuses on the implementation of the Non-Cash Food Assistance (BPNT) policy in poverty alleviation efforts in Kembangan District, West Jakarta, during the COVID-19 pandemic. While the BPNT program managed by the Ministry of Social Affairs of the Republic of Indonesia adheres to the distribution procedures, several challenges have emerged, including delays in disbursing aid funds, invalid beneficiary data, issues with E-waroeng (food stalls), account registration, delayed distribution, and occasional inadequacy of food supplies. However, supportive factors such as effective coordination, improved data management, education, active participation from local authorities, and the commitment of E-waroeng owners have contributed to the program's success and maximized its benefits for beneficiaries. Efforts to address these challenges and ensure enhanced efficiency and timeliness in BPNT program implementation are essential.